Strategi Komunikasi Pemasaran Dalam Meningkatkan Jumlah Penginap Di Hotel Best Skip Palembang - Hambali Hambali; Gita Astrid; Yustika Utari (Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study aims to determine the marketing strategy carried out by the Best Skip Hotel in increasing the number of residents. Best Skip Hotel is a 2 star Hotel located in the center of Palembang. Best Skip Hotel has complete facilities with cheap and affordable tariffs for all people. The methods used in this research is to use descriptive qualitative methods, data collection techniques conducted by researchers through interviews, documentation, and observation. Primary data sources in this study are the General Manager, Marketing Team, Hotel visitors, and Hotel staff and employees. While the secondary data source is in the form of documents, organizational structure, and books related to research. The Hotel implements several communication models such as direct and indirect communication. Direct communication conducted by this Hotel is in the form of Sales Promotion, Personal Selling, and Direct Selling. While the indirect communication made by this Hotel is by using promotions through social media such as Facebook, Tweeter, Instagram, the internet, brochures, and so on. The Best Skip Palembang Hotel adopts a strategy that is more focused on promotional activities, but the Hotel also strives to maximize the quality of its products, facilities, price, and services in order to meet customer needs. Marketing promotion activities carried out by Marketing at the Best Skip Hotel are through promotional banners and internet promotions, because these promotional activities cost relatively cheaply but can have maximum results. The internal activities of the Hotel every day hold daily meetings to monitor how the development and condition of the Hotel. The next strategic process is by analyzing the situation by Marketing and Hotel Managers such as conducting research by analyzing Income Audit reports or daily income in the form of finances and the number of guests staying. In addition, the Marketing also monitors customer feedback or responses through customer comments on the Hotel Website. Factors that influence the stay at the Best Skip Hotel is because this Hotel has a cheap price and fairly complete facilities.